Antioxidant and anti-inflammatory effects of curcumin against hepatorenal oxidative injury in an experimental sepsis model in rats - DULUNDU, ENDER; ERCAN, FERİHA; ŞENER, GÖKSEL (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2013)
BACKGROUND: To investigate the effects of curcumin, an antioxidant and anti-inflammatory agent, on free oxygen radicals and lipid peroxidation in an experimental sepsis model, as well as to determine the role of curcumin in preventing hepatorenal tissue damage caused by sepsis. METHODS: The rats were randomly divided into three groups (n=8) as follows: control group (group 1); sepsis group (group 2); and sepsis + curcumin group (group 3). Sepsis was created using the cecal ligation and perforation (CLP) method. Curcumin was administered intraperitoneally (200 mg/kg) in two equal doses just after the perforation and at twelve hours post-perforation. RESULTS: Serum TNF-alpha and IL-1 beta, and tissue MDA and MPO values were higher, whereas tissue GSH and Na+/K+-ATPase values were lower, in group 2 as compared to group 1. These values in group 3 were the inverse of those in group 2. As compared to group 1, histopathological evaluation of group 2 showed damaged hepatocytes, glomeruli, and tubules, whereas the damage was significantly reduced in group 3 as compared to group 2. CONCLUSION: The strong antioxidant and anti-inflammatory effects of curcumin against potential hepatorenal damage were shown using an experimental sepsis model in rats.
Keywords: Curcumin; free oxygen radicals; sepsis; MORTALITY; OCCLUSION; ISCHEMIA; ATPASE; DAMAGE